Intrinsic photo-degradation and mechanism of polymer solar cells: the crucial role of non-fullerene acceptors - Park, Sungmin; Son, Hae Jung (ROYAL SOC CHEMISTRY, 2019)
The performances of polymer solar cells (PSCs) based on non-fullerene acceptors (NFAs) have improved remarkably in recent years, but such devices are insufficiently stable for practical applications. Here, we investigated the effects of NFAs on PSC long-term stability. We found that high performance PBDB-T : ITIC solar cells exhibit much lower stability than PTB7 : PC71BM devices in the 1 sunlight-soaking test; when compared with their initial performances, the performance of PTB7 : PCBM-based solar cells remains above 60% for over 4000 h, whereas that of PBDB-T : ITIC-based devices is reduced to one fifth after 1000 h. We demonstrated that the ITIC-based PSCs exhibit poor photo-stability because ITIC at the interface of the ZnO/active film is readily decomposed by a photocatalytic reaction; this poor stability arises because the vinyl group of ITIC is chemically more vulnerable than the stable aromatic units in the organic active materials. The decomposition of ITIC results in the degradation of the electron transport properties of the active materials located close to ZnO, which leads to severe burn-in degradation and reduced FF and V-OC under illumination. It is thus highly important to develop intrinsically stable organic materials composed of chemically stable building blocks in order to realize stable and high efficiency PSCs.
Keywords: ENERGY-LEVEL MODULATION; ELECTRON-ACCEPTORS; OXYGEN VACANCIES; EFFICIENCY; STABILITY; VOLTAGE; ZNO; WETTABILITY; GENERATION